Prevalence and management of hypertension in Turner syndrome: data from the International Turner Syndrome (I-TS) registry - Shani A D Mathara Diddhenipothage; Katharina J Beck; Gayana Amiyangoda; Jillian Bryce; Luminita Cima; Katya De Groote; Yana Deyanova; Evgenia Globa; Gloria Herrmann; Anders Juul; Anna Sophie L Kjaer; Anette Tønnes Pedersen; et al. (Endocrine Connections)
Introduction: Cardiovascular disease is the most common cause of death in Turner syndrome (TS) for which arterial hypertension has a direct influence and is a key modifiable risk factor. Objective: To investigate the prevalence and patterns of hypertension diagnosis and management in adult patients with TS who are registered in a large international multicentre database (TS-HTN study). Methods: Retrospective multicentre observational study of patients aged ≥18 years included in the I-TS (International-TS) registry (2020–2022), using registry and participating centre-collected data. Results: Twelve international centres participated, including 182 patients with a median age of 28 years (IQR 23–37.2). Arterial hypertension was recorded in 13.2% (n = 24). The median age at hypertension diagnosis was 27 years (range 10–56), with 92% aged less than 50 years at diagnosis. The majority (75%) were classified as primary hypertension (n = 18). In binomial regression analysis, higher body mass index was the only parameter significantly associated with the occurrence of hypertension (B = 1.487, P = 0.004). Among patients with aortic disease (n = 9), 50% had systolic BP ≥ 130 mmHg and 66.6% had diastolic BP ≥ 80 mmHg during the last clinic review. Angiotensin-converting enzyme inhibitors were the most common (n = 16) medication prescribed, followed by angiotensin receptor blockers (n = 6), beta-blockers (n = 6) and calcium channel blockers (n = 6). Conclusions: Arterial hypertension is common in TS and occurs at a young age. Overweight/obesity was a notable risk factor for hypertension. The frequency of suboptimal BP control among high-risk patients highlights the importance of increased awareness and TS-specific consensus guidance on management.